Multiculturalism and brain drain. - Nur Izyan Ismail. (2009)
This study aimed to analyze the relationship between multiculturals and brain drain and, its possible reasons. Two identification orientation measures were used; difference measure and interaction measure. For difference measure, it was predicted the higher individuals scored on western identity relative to national categorical identity, the higher their emigration intention. For interaction measure, it was expected that the two identities would interact to predict emigration intention. These relationships were expected to be moderated by the receiving country’s perceived westernization. Results supported hypothesis for the relationship between the difference measure and intention to emigrate and, it was moderated by the country’s perceived westernization. All three mediators were found not to mediate. For interaction measure, all hypotheses were not supported.